Comparison of various intensity levels for variable resistance countermovement jump on inducing postactivation potentiation - Chen, Siow Ee (2019)
Postactivation potentiation (PAP) is a phenomenon that involves the preconditioning of muscles through conditioning activities (CAs) to induce acute improvements in performance. The purpose of this study was to establish the optimum variable resistance level for loaded countermovement jump (LCMJ) to induce PAP. It was hypothesized that the resistance level associated with the highest peak power during the LCMJ would induce the greatest PAP effect. In this study, 12 male resistance trained competitive power-based sports athletes from Singapore Sport Institute and Nanyang Technological University (Age = 24.33 ± 2.50 years; Height = 1.76 ± 0.06 m; Body Mass = 73.71 ± 8.56 kg; Body Mass Index = 23.70 ± 1.97 kg/m2) were recruited. They went through four different conditions: countermovement jump (CMJ) with no load (control), LCMJ with light band (orange), medium band (red) or heavy band (blue) in a randomized crossover manner to compare the effects of various intensity levels for LCMJ on inducing PAP. Findings showed no significant difference in mean of pre and posttest jump height (p = .187), peak power output (p = .372) and peak velocity (p = .337) across four different conditions, however, there was a significant difference in the mean of pre and posttest peak force (p = .019) between conditions. In conclusion, performing LCMJ improved peak force production but not other variables hence it was not an effective CA to be used to improve subsequent jumping performance.